2022
DOI: 10.1002/eat.23874
|View full text |Cite
|
Sign up to set email alerts
|

Development of a brief cognitive‐behavioral treatment for avoidant/restrictive food intake disorder in the context of disorders of gut–brain interaction: Initial feasibility, acceptability, and clinical outcomes

Abstract: Background: Avoidant/restrictive food intake disorder (ARFID) symptoms are common (up to 40%) among adults with disorders of gut-brain interaction (DGBI), but treatments for this population (DGBI + ARFID) have yet to be evaluated.We aimed to identify initial feasibility, acceptability, and clinical effects of an exposure-based cognitive-behavioral treatment (CBT) for adults with DGBI + ARFID. Methods: Patients (N = 14) received CBT as part of routine care in an outpatient gastroenterology clinic. A two-part in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…This may reflect differences in nutritional state between AN and BN. Findings extend work suggesting that the prevalence of DGBI and gastrointestinal symptoms generally decrease during inpatient treatment for BN (Chami et al, 1995; Salvioli et al, 2013) and data demonstrating reductions in fullness and satiation among individuals with avoidant/restrictive food intake disorder and DGBI during cognitive behavioral therapy (Burton Murray et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…This may reflect differences in nutritional state between AN and BN. Findings extend work suggesting that the prevalence of DGBI and gastrointestinal symptoms generally decrease during inpatient treatment for BN (Chami et al, 1995; Salvioli et al, 2013) and data demonstrating reductions in fullness and satiation among individuals with avoidant/restrictive food intake disorder and DGBI during cognitive behavioral therapy (Burton Murray et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…Up to 40% of DGBI patients meet criteria for symptoms of ARFID, 9 particularly those with a history of restrictive diets 10 . While ARFID‐like symptoms are common among DGBI patients, we found only eight papers that meet keywords for both ARFID and DGBI on PubMed to date 9,11–17 . In addition, since ARFID has been first described by the DSM‐5 in 2013, the current literature on this eating disorder among adult population is very limited.…”
Section: Discussionmentioning
confidence: 94%
“…10 While ARFID-like symptoms are common among DGBI patients, we found only eight papers that meet keywords for both ARFID and DGBI on PubMed to date. 9,[11][12][13][14][15][16][17] In addition, since ARFID has been first described by the DSM-5 in 2013, the current literature on this eating disorder among adult population is very limited. Studies are heterogeneous with regard to their methodology.…”
mentioning
confidence: 99%
“…20 In fact, one small study showed among adults with disorders of gut-brain interaction with ARFID (n = 7 of whom had functional dyspepsia) that a behavioral treatment aimed at increasing food intake was associated with large reductions in PAGI-SYM fullness/satiety scores. 21 Considering the similarities in symptoms of ARFID and Gp and the distinctly different management strategies for each disorder, it is important to continue to investigate the relationship and causal- This study has potential limitations. As noted above, we used NIAS score cutoffs validated in a prior study; however, this validation study was done in an ARFID clinical sample, not a sample of adults with Gp who were diagnosed with ARFID.…”
Section: Discussionmentioning
confidence: 99%